Syngas Production in a Sequential Fixed-bed Reactor Network Using Chemical Looping Reforming: A Numerical Analysis - Mohammad Rahmani; Sanaz Moradi Soltani; Hadi Ebrahimi (Journal of Petroleum Science and Technology)
Chemical looping reforming is a new technology for hydrogen or synthesis gas (syngas) production with lower CO2 emission and energy usage than conventional routes such as methane steam reforming. In this study, the numerical analysis of syngas production in a packed-bed reactors’ network is presented. Moreover, the proposed layout consists of four parallel reactors performing oxidation, reduction, and purge operations. In addition, both nickel and perovskite particles are used as the oxygen carrier. Furthermore, methane and oxygen were employed as fuel and oxidizer to produce H2 and CO continuously. In addition, with the proper selection of temperature and reduction time, a dynamic study was carried out to evaluate the feasibility of the proposed system in terms of methane conversion (about 1), H2 yield (about 0.65 mole H2/mole CH4), average syngas ratio (about 4 mole H2/mole CO) and zero carbon dioxide at the reactor output. In the end, a switching system of the network is proposed for continuous syngas production..